Characterization of surface-plasmon modes in metal-clad optical waveguides - Kalli, Kyriacos; Themistos, Christos; Rajarajan, Muttukrishnan; Rahman, Bilkish M Azizur; Grattan, Kenneth Thomas Victor (My University, 2006)
Finite-element analysis, based on the vector H-field formulation and incorporating the perturbation technique, is used to calculate the complex propagation characteristics of metal-coated dielectric waveguides. The propagation and attenuation characteristics of the surface-plasmon modes at the metal/dielectric interfaces are presented. The effects on the optical properties of metal-clad optical fibers with infinite and finite cladding thickness and the formation of the supermodes due to the coupling between the surface-plasmon modes in the presence of different surrounding materials are also investigated.
Keywords: Electromagnetic waves; Finite element method; Metal cladding; Optical fibers; Surface plasmon resonance; Optical wave guides